A pH‐Responsive Cluster Metal–Organic Framework Nanoparticle for Enhanced Tumor Accumulation and Antitumor Effect. Issue 42 (13th September 2022) - Cheng, Ruoyu; Jiang, Lingxi; Gao, Han; Liu, Zehua; Mäkilä, Ermei; Wang, Shiqi; Saiding, Qimanguli; Xiang, Lei; Tang, Xiaomei; Shi, Minmin; Liu, Jia; Pang, Libin; et al.
Abstract: As a result of the deficient tumor‐specific antigens, potential off‐target effect, and influence of protein corona, metal–organic framework nanoparticles have inadequate accumulation in tumor tissues, limiting their therapeutic effects. In this work, a pH‐responsive linker (L) is prepared by covalently modifying oleylamine (OA) with 3‐(bromomethyl)‐4‐methyl‐2, 5‐furandione (MMfu) and poly(ethylene glycol) (PEG). Then, the L is embedded into a solid lipid nanoshell to coat apilimod (Ap)‐loaded zeolitic imidazolate framework (Ap‐ZIF) to form Ap‐ZIF@SLN#L. Under the tumor microenvironment, the hydrophilic PEG and MMfu are removed, exposing the hydrophobic OA on Ap‐ZIF@SLN#L, increasing their uptake in cancer cells and accumulation in the tumor. The ZIF@SLN#L nanoparticle induces reactive oxygen species (ROS). Ap released from Ap‐ZIF@SLN#L significantly promotes intracellular ROS and lactate dehydrogenase generation. Ap‐ZIF@SLN#L inhibits tumor growth, increases the survival rate in mice, activates the tumor microenvironment, and improves the infiltration of macrophages and T cells in the tumor, as demonstrated in two different tumor‐bearing mice after injections with Ap‐ZIF@SLN#TL. Furthermore, mice show normal tissue structure of the main organs and the normal serum level in alanine aminotransferase and aspartate aminotransferase after treatment with the nanoparticles. Overall, this pH‐responsive targeting strategy improves nanoparticle accumulation in tumors with enhanced therapeutic effects. Abstract : A pH‐responsive metal–organic framework nanoparticle responsively removes hydrophilic compositions with steric hindrance and exposes the hydrophobic part in situ, forming clustering nanoparticles with enhanced tumor accumulation and therapeutic effects.